The Role of the Studi Independen Program in Enhancing Students' Job Readiness - Rhiansyah, Ariadafa Wahyu (Proceeding Kilisuci International Conference on Economic & Business, 2025)
Research aim : To evaluate the impact of the Studi Independen Program on students' skills and job readiness from the perspectives of students and business actors. Design/Methode/Approach : Qualitative descriptive research with structured interviews. Informants were selected using the 4R technique. Research Finding : The Studi Independen Program enhances students' technical and interpersonal competencies, though there are shortcomings in advanced skill development and guidance for professional portfolio creation. Data analysis involved reduction, categorization, and triangulation to ensure validity. The research was conducted through online interviews and establishment in Kediri City. Theoretical contribution/Originality : Provides an evaluation of the program's impact from two perspectives. Practitionel/Policy implication : Offers insights to improve experiential learning programs in alignment with industry needs. Research limitation : Limited participant coverage and a qualitative approach may not fully reflect broader experiences.